Phytochemical compound identification and anti-infertility property of n-miracle (polyherbal formulation) by uv-visible spectroscopy, ftir, tlc, hplc and gc-ms study - MEENATCHI SUNDARAM ANGAPPAN,; JEYAPRAKASH KARUPPAIAH, (International Journal of Pharma and Bio Sciences, 2017)
Male infertility is a world-wide medical and social problem. In Ayurveda, single or multiple herbs (polyherbal) are used for the treatment. The concept of polyherbalism is to achieve greater therapeutic efficacy. The active phytochemical constituents of individual plants are insufficient to achieve the desirable therapeutic effects. When combining the multiple herbs in a particular ratio, it will give a better therapeutic effect and reduce the toxicity. N-Miracle, a polyherbal formulation, which was prepared by the combination of five medicinal plants and selenium having diversified pharmacological effect, however, the anti-infertility effect of the combination of the above plants are not yet carried out. Hence, the present study has been designed with the purpose of identifying the active principles of methanolic extract of N-Miracle (Polyherbal formulation) by UV-Visible spectrophotometer, FTIR, TLC, HPLC, and GC-MS analysis. UV-Visible spectrum revealed the presence of phenolic compounds and flavonoid compounds in the range of 220 nm to 1100 nm. FTIR spectrum unveiled the presence of phenol, alkane, carboxylic acid, aromatic compound, aliphatic amines and halogen compounds. TLC of methanolic extract of N-Miracle (Polyherbal formulation) revealed the presence flavonoid compound namely isoquercetin. HPLC analysis of the methanolic extract of N-Miracle (Polyherbal formulation) showed the presence of polyphenols and flavonoid compound at RT 5.541, RT 13.060, and RT 32.028. GC-MS screening revealed the presence of alcohol, fatty alcohol, alkane, phytol, and fatty acid methyl esters groups.